Feasibility Study of Utilizing Ultraportable Projectors for Endoscopic Video Display (With Videos). (October 2014) - Tang, Shou-jiang; Fehring, Amanda; Mclemore, Mac; Griswold, Michael; Wang, Wanmei; Paine, Elizabeth R.; Wu, Ruonan; To, Filip
Background . Modern endoscopy requires video display. Recent miniaturized, ultraportable projectors are affordable, durable, and offer quality image display. Objective . Explore feasibility of using ultraportable projectors in endoscopy. Methods . Prospective bench-top comparison; clinical feasibility study. Masked comparison study of images displayed via 2 Samsung ultraportable light-emitting diode projectors (pocket-sized SP-HO3; pico projector SP-P410M) and 1 Microvision Showwx-II Laser pico projector. Bench-top feasibility study : Prerecorded endoscopic video was streamed via computer. Clinical comparison study : Live high-definition endoscopy video was simultaneously displayed through each processor onto a standard liquid crystal display monitor and projected onto a portable, pull-down projection screen. Endoscopists, endoscopy nurses, and technicians rated video images; ratings were analyzed by linear mixed-effects regression models with random intercepts. Results . All projectors were easy to set up, adjust, focus, and operate, with no real-time lapse for any. Bench-top study outcomes : Samsung pico preferred to Laser pico, overall rating 1.5 units higher (95% confidence interval [CI] = 0.7-2.4), P < .001; Samsung pocket preferred to Laser pico, 3.3 units higher (95% CI = 2.4-4.1), P < .001; Samsung pocket preferred to Samsung pico, 1.7 units higher (95% CI = 0.9-2.5), P < .001. The clinical comparison study confirmed the Samsung pocket projector as best, with a higher overall rating of 2.3 units (95% CI = 1.6-3.0), P < .001, than Samsung pico. Conclusions . Low brightness currently limits pico projector use in clinical endoscopy. The pocket projector, with higher brightness levels (170 lumens), is clinically useful. Continued improvements to ultraportable projectors will supply a needed niche in endoscopy through portability, reduced cost, and equal or better image quality.